2016
DOI: 10.4142/jvs.2016.17.4.459
|View full text |Cite
|
Sign up to set email alerts
|

Physical-chemical and biological characterization of different preparations of equine chorionic gonadotropin

Abstract: Ovarian stimulation with commercial preparations of equine chorionic gonadotropin (eCG) produces extremely variable responses in domestic animals, ranging from excessive stimulation to practically no stimulation, when applied on the basis of their declared unitage. This study was conducted to analyze four commercial preparations from different manufacturers via reversed-phase HPLC (RP-HPLC) in comparison with a reference preparation and an official International Standard from the World Health Organization. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(43 reference statements)
0
4
0
2
Order By: Relevance
“…La respuesta superovulatoria fue muy variable, encontrándose hembras con 1 a 9 folículos pos-tratamiento, lo cual está ampliamente descrito en camélidos (Ratto et al, 2013). Este resultado podría estar influenciado, además, por la alta variabilidad de la concentración de la hormona eCG en los preparados comerciales (Herrera et al, 2016).…”
Section: Resultados Y Discusiónunclassified
“…La respuesta superovulatoria fue muy variable, encontrándose hembras con 1 a 9 folículos pos-tratamiento, lo cual está ampliamente descrito en camélidos (Ratto et al, 2013). Este resultado podría estar influenciado, además, por la alta variabilidad de la concentración de la hormona eCG en los preparados comerciales (Herrera et al, 2016).…”
Section: Resultados Y Discusiónunclassified
“…Alvarez et al. () reported that different commercial preparations of this hormone may differ in their physico‐chemical profile determined by reverse‐phase high pressure liquid chromatography (RP‐HPLC) and their in vivo bioactivity in prepubertal female rat and peripubertal gilt models.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, eCG preparations from different manufacturers were used in the two studies. Alvarez et al (2016) reported that different commercial preparations of this hormone may differ in their physicochemical profile determined by reverse-phase high pressure liquid T A B L E 2 Effects of application time (days postpartum) of equine chorionic gonadotropin on calving to first service and calving to conception interval within study group eCG (Cox regression analysis) chromatography (RP-HPLC) and their in vivo bioactivity in prepubertal female rat and peripubertal gilt models.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin can increase metabolism, maximize vitellogenin synthesis, stimulate feed consumption, endogenous secretion, and poultry productivity (Park et al, 2012). Meanwhile, PMSG hormone has high effectiveness in stimulating superovulation because it has multiple actions, such as FSH and LH (Alvarez et al, 2016). P3 ducks during the 3rd laying period had the lowest egg production, presumably because the experimental ducks experienced physiological stress due to the first injection of PMSG.…”
Section: Egg Productivitymentioning
confidence: 99%